Glucosamine-sulfate on fracture healing - Uğraş, Akın; Güzel, Elif; Korkusuz, Petek; Kaya, İbrahim; Dikici, Fatih; Demirbaş, Emrah; Çetinüs, Ercan (Turkısh Assoc Trauma Emergency Surgery, 2013)
BACKGROUND The aim of this study is to determine whether glucosamine-sulfate has any effects on bone-healing. METHODS A unilateral fracture was created in the tibia of sixty-one female rats. Rats were given no drug or 230 mg/kg glucosamine- sulfate daily. Fractures were analyzed during the first, second and fourth weeks after creation of fracture. Quantitative measurement for new bone formation and osteoblast lining were determined histologically. Semiquantitative score for fracture healing was used for histomorphometric analyses. Bridging bone formation was assessed radiographically. RESULTS New bone formation and osteoblast lining were significantly higher in glucosamine-treated group at week 1. Surrounding connective tissue was more cellular and vascular, and the newly formed bone trabecules were present in greater amounts in glucosamine-treated group, compared to control group at week 1 and 4. But radiologically, the control group had better scores than that of the glucosamine- treated group at week 4. CONCLUSION These data demonstrate that daily glucosamine-sulfate administration accelerates early phase of fracture repair in the rat tibia, with increased new bone formation and osteoblast lining histologically, but radiologic bone union is not favored on radiographs.

Bu çalışmanın amacı kıkırdak glukozaminin kırık iyileşmesi üzerinde etkisi olup olmadığının araştırılmasıdır. GEREÇ VE YÖNTEM Altmış bir dişi şıçan tibiasında tek taraflı kırık oluşturuldu. Sıçanlara ya 230 mg/kg glukozamin sülfat verildi ya da ilaç verilmedi. Kırıklar, kırık oluşumundan sonra birinci, ikinci ve dördüncü haftalarda incelendi. Yeni kemik oluşum miktarı ve osteoblast sayısı histolojik olarak ölçüldü. Histomorfometrik analiz için kırık iyileşmesi semikantitatif olarak skorlandı. Radyografik olarak kemik köprü oluşumu değerlendirildi. BULGULAR Glukozamin verilen grupta yeni kemik oluşumu ve osteoblast sayısı 1. haftada anlamlı derecede yüksekti. 1. ve 4. haftalarda kontrol grubuna göre, glukozamin verilen grupta çevre bağ dokusu hücre sayısı bakımından zengin, daha vasküler ve yeni oluşan kemik trabekülleri daha fazla sayıdaydı. Fakat radyolojik olarak 4. haftada kontrol grubu, glukozamin verilen gruptan daha iyi skorlar aldı. SONUÇ Bu veriler günlük glukozamin verilmesinin sıçan tibiasında kırık iyileşmesinin erken fazını, artmış yeni kemik oluşumu ve osteoblast sayısı ile histolojik olarak hızlandırdığı, fakat radyolojik olarak aynı etkinin görülmediğini göstermektedir
Glukozamin sülfatın kırık iyileşmesine etkisi
WOS: 000315847100002
PubMed ID: 23588972
Keywords: Bone; Fracture Healing; Glucosamine; Osteoblast; Kemik; Kırık İyileşmesi; Glukozamin